Katharina Völker, Quran and Reform: Rahman, Arkoun, Abu Zayd. (25th January 2019) - Marcotte, Roxanne
Abstract : Katharina Völker, Quran and Reform: Rahman, Arkoun, Abu Zayd. Frankfurt am Main: Peter Lang BmbH, 2017, pp. 195, ISBN: 978-3-631-67531-1 (pbk).